Equilibrium Liquid Crystal Phase Diagrams and Detection of Kinetic Arrest in Cellulose Nanocrystal Suspensions - Honorato-Rios, Camila; Kuhnhold, Anja; Bruckner, Johanna R.; Dannert, Rick; Schilling, Tanja; Lagerwall, Jan P. F. (Frontiers in Materials, 2016)
The cholesteric liquid crystal self-assembly of water-suspended cellulose nanocrystal (CNC) into a helical arrangement was observed already more than 20 years ago, and the phenomenon was used to produce iridescent solid films by evaporating the solvent or via sol–gel processing. Yet, it remains challenging to produce optically uniform films and to control the pitch reproducibly, reflecting the complexity of the three-stage drying process that is followed in preparing the films. An equilibrium liquid crystal phase formation stage is followed by a non-equilibrium kinetic arrest, which in turn is followed by structural collapse as the remaining solvent is evaporated. Here, we focus on the first of these stages, combining a set of systematic rheology and polarizing optics experiments with computer simulations to establish a detailed phase diagram of aqueous CNC suspensions with two different values of the surface charge, up to the concentration where kinetic arrest sets in. We also study the effect of varying ionic strength of the solvent. Within the cholesteric phase regime, we measure the equilibrium helical pitch as a function of the same parameters. We report a hitherto unnoticed change in character of the isotropic–cholesteric transition at increasing ionic strength, with a continuous weakening of the first-order character up to the point where phase coexistence is difficult to detect macroscopically due to substantial critical fluctuations.